CONSTRUCTION CONTRACT OF HIRE PURCHASE AND CORRELATION WITH CRIMINAL OFFENSE - Bambang Tri Bawono (International Journal of Law Reconstruction, 2019)
Hire purchase agreements that have developed in the realm of society yet have clarity because there is no specific legislation governing the lease-sale agreement. The absence of specific legislation governing the lease resulted in the agreement to experience different views for legal experts both in terms of the definition and the legal consequences arising. This type of research used in this study is a research library with normative juridical approach. Normative research. The results of this study mention: first, the legal construction of a hire purchase agreement did not have legal certainty, because this agreement has legal consequences of changing from the payment of the debt to the payment of rent, when a tort committed by the purchaser. Other than that, construction law hire purchase agreement is null and void, because there are some clauses which are contrary to Article 1266 of the Civil Code and Article 18 of the Consumer Protection Act. Second, the criminal offenses arising from a lease agreement is a criminal offense of extortion, when the withdrawal unilaterally, although financing the vehicle has been registered in the Register of Fiduciary. This is because even though the fiduciary has the right of executor, but the execution must follow procedures for the implementation of a court decision, so businesses must apply in advance to the Chairman of the Court.